2011
DOI: 10.1016/j.jana.2011.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus and Anorectal Carcinoma Knowledge in Men Who Have Sex With Men

Abstract: Human papillomavirus (HPV) infection is a precursor to the development of anorectal carcinoma. Studies have indicated that men who have sex with men (MSM) have significantly higher rates of HPV and HIV than their heterosexual counterparts and are at greater risk for anorectal carcinoma. This article presents findings from a descriptive study to assess knowledge of HPV, anorectal carcinoma, and anorectal screening in a sample of MSM in Orlando, FL. The 89 participants demonstrated knowledge deficits. The averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Our study results support findings from previous work showing the limited HPV knowledge among men and women from several countries [25][27], including MSM from the US, Denmark, Australia and [16], [28][31]. Overall, our data coincide with several studies indicating that most men are unaware that GW are caused by HPV infection [13], [30], [32][33].…”
Section: Discussionsupporting
confidence: 91%
“…Our study results support findings from previous work showing the limited HPV knowledge among men and women from several countries [25][27], including MSM from the US, Denmark, Australia and [16], [28][31]. Overall, our data coincide with several studies indicating that most men are unaware that GW are caused by HPV infection [13], [30], [32][33].…”
Section: Discussionsupporting
confidence: 91%
“…Men passively acquired information in 13 studies: 4 quantitative, 2 qualitative, and 1 mixed‐methods study on prostate cancer screening; 3 qualitative studies and 1 quantitative study on colorectal cancer screening; 1 quantitative study on human papilloma virus and anorectal cancer prevention; and 1 qualitative study on general cancer information …”
Section: Resultsmentioning
confidence: 99%
“…For instance, participants in 2 qualitative studies identified their physician as the primary source of information about colorectal cancer . Blackwell et al surveyed 89 men who have sex with men about their awareness of human papilloma virus and anorectal cancer . It was found that 49 participants had heard of anal Pap smears from different sources, including their primary care physician (10.2%), nurse (16.3%), and other health care professionals (32.7%) .…”
Section: Resultsmentioning
confidence: 99%
“…11 Later, Blackwell and Eden conducted a similar study with a sample of 89 MSM in the United States. 12 Data were summarized descriptively as percentages or means (M) and standard deviations (SD). The relationships between HPV knowledge and awareness of anal cancer risk with demographic and anal health self-care behaviors/ practices/perceptions variables were analyzed using Pearson's correlations and one-way analysis of variance (ANOVA).…”
Section: Methodsmentioning
confidence: 99%
“…In response to their findings, the authors proposed a targeted health education campaign to increase anal cytology screening for sexually active MSM, and particularly for HIV-infected MSM. In a later United States study, Blackwell and Eden, 12 using the same survey measure as Pitts and colleagues, 11 sampled 89 MSM. The authors reported knowledge deficits with 38% correct as the average score on the knowledge items.…”
Section: Introductionmentioning
confidence: 99%